MtDNA genetic diversity and phylogeographic insights into giant domestic pigeon (Columba livia domestica) breeds: connections between Central Europe and the Middle East - K. Balog; A.S. Wadday; B.A. Al-Hasan; G. Wanjala; Sz. Kusza; P. Fehér; V. Stéger; Z. Bagi (Poultry Science, 2024)
ABSTRACT: Humans have selectively bred domestic pigeons (Columba livia domestica) to create breeds with a diversity of shapes, colors and other attributes. Since Darwin, the domestic pigeon has always been a popular model species for scientific research because of its richness of form, colouration and behaviour. It is believed that the world's squab pigeon industry uses breeds and hybrids from the Mediterranean region. An exception is the indigenous giant pigeon breeds of the Carpathian Basin, whose origin is not known. Therefore, our aims were 1) to understand the phylogenetic relationships of giant pigeons, which sheds light on the origin of Hungarian breeds and their relationship to the Mediterranean giant pigeon breed group; 2) to contribute molecular genetic data to the genealogy of 2 Iraqi pigeon breeds close to the pigeon domestication center, including the culturally important Iraqi Red Pigeon, and 3) to compare the genetic diversity of European and Middle Eastern domestic pigeon populations and to draw conclusions on the phylogenetic relationships between pigeon breeds and molecular clues to their different breeding practices of both regions. A 655-bp-long sequence of the cytochrome oxidase 1 (COI) region of the mitochondrial DNA was studied in a total of 276 pigeons (19 breeds). A total of 27 haplotypes were found, of which 22 were unique. The highest genetic diversity was found in the Carpathian Basin, and the lowest in the Iraqi region. STRUCTURE analysis revealed low structurality, K=3 was the most likely. The majority of the samples belong to the most ancient haplotype H_2=219, however the Jacobin pigeon is on a very separate evolutionary branch with a large number of mutations. None of the 19 breeds investigated in this study have been previously studied in phylogenetics, and most of these breeds have potential as squab pigeons, and have good meat forms for utilization, therefore the results of this study may also be of help to the squab pigeon industry.